2022
DOI: 10.1159/000525493
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Disaggregated Analysis of Biology, Treatment Tolerability, and Outcome of Multiple Myeloma in a German Cohort

Abstract: Introduction: Multiple Myeloma (MM) is a plasma cell disease that affects more men than women. Although there is an obvious imbalance in incidence, knowledge on differences in biology and outcome between the sexes is surprisingly rare. Methods: We performed a unicentric retrospective analysis of patients with MM treated at a tertiary cancer center between 2003 and 2018. Results: We present sex-disaggregated analysis of the characteristics and outcome of MM in a cohort of 655 patients (median age at diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
1
0
3
Order By: Relevance
“…Für das MM sind folgende Geschlechtsunterschiede bekannt: Frauen erkranken seltener und später und haben häufiger eine ungünstige Risikokonstellation [28,29]. Außerdem haben sie im Durchschnitt niedrigere Hämoglobinwerte, was bedeutet, dass sie häufiger eine schwere Anämie aufweisen [28].…”
Section: Zusatzinfounclassified
See 2 more Smart Citations
“…Für das MM sind folgende Geschlechtsunterschiede bekannt: Frauen erkranken seltener und später und haben häufiger eine ungünstige Risikokonstellation [28,29]. Außerdem haben sie im Durchschnitt niedrigere Hämoglobinwerte, was bedeutet, dass sie häufiger eine schwere Anämie aufweisen [28].…”
Section: Zusatzinfounclassified
“…Für das MM sind folgende Geschlechtsunterschiede bekannt: Frauen erkranken seltener und später und haben häufiger eine ungünstige Risikokonstellation [28,29]. Außerdem haben sie im Durchschnitt niedrigere Hämoglobinwerte, was bedeutet, dass sie häufiger eine schwere Anämie aufweisen [28]. Andererseits haben Frauen mit MM seltener Begleiterkrankungen, was einer der Gründe darstellen könnte, warum trotz des höheren Alters und der ungünstigen MM-Risikokonstellation Frauen kein schlechteres Überleben als Männer haben [29].…”
Section: Zusatzinfounclassified
See 1 more Smart Citation
“…The prevalence of MG increases with age, several studies have reported a mean age at the time of diagnosis of 68 years, and most of them (99%) were over 40 years old 1,2 . It affects men more than women, 3 and black race more than white. In a South African study on the prevalence of MGUS (Monoclonal gammopathy of undetermined signification) among 386 Black men, the prevalence of MGUS was significantly higher (8.03% [95% confidence interval (CI), 5.32–10.74]) in comparison to white men from Olmsted in the United States (2.97%, (95% CI, 2.59–3.34)) 4 …”
Section: Introductionmentioning
confidence: 99%